Prevalence of Imaging Detected Silent Male Breast Cancer in Autopsy Specimens: Study of the Disease Held by Image-Guided Biopsies. Issue 1 (March 2023) - Sidiropoulou, Zacharoula; Vasconcelos, Ana Paula; Couceiro, Cristiana; Santos, Carlos Dos; Araújo, Ana Virginia; Alegre, Inês; Santos, Claudia; Costa, Filipa; Cardoso, Diogo; Cardoso, Vasco; Sampaio, Rita; Cardoso, Fátima; et al.
Introduction: Regarding male breast cancer, a rare disease comprising ∼1% of breast cancers, data are generally scant. The present study aimed to quantify the imaging detected breast cancer in male gender corpses, determining in this way the prevalence of silent breast cancer in male gender. Methodology: The population target has been male corpses without clinical expression of breast cancer. Seventy-four male corpses have been submitted to bilateral subcutaneous radical mastectomy. Samples have been submitted to echography and mammography imaging and every lesion superior to BI-RADS 4a has been excised. Results: One excisional biopsy has been performed and no case of breast cancer has been identified. Discussion: Our findings suggest that screening of the general population for male breast cancer is not necessary.